BUILDING INCLUSIVE AND EQUITABLE ORGANIZATIONS: A SYSTEMATIC REVIEW OF DEI INITIATIVES, IMPLEMENTATION CHALLENGES, AND FUTURE PATHWAYS - Teddy Chandra Simanjuntak; Sopiansyah Sopiansyah; Josua Parulian Sinaga; Yudhi Winardi; Tetra Hidayati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study examines the current landscape of Diversity, Equity, and Inclusion (DEI) initiatives in organizational settings. The review aims to synthesize empirical evidence on how contemporary DEI strategies operate and assess their effectiveness across sectors during the period 2020–2025.Methods: This study adopts a systematic literature review design following PRISMA guidelines. Articles were retrieved from Scopus, Web of Science, and Google Scholar databases within the publication range of 2020–2025. Inclusion criteria covered peer-reviewed empirical studies focusing on DEI implementation at the organizational level, published in English. Exclusion criteria included conceptual papers, opinion pieces, non-organizational settings, and studies without explicit DEI outcomes. From 1,246 initial records, 78 studies met the eligibility criteria. Data were analyzed using thematic synthesis, supported by narrative integration. Quality appraisal was conducted using the Critical Appraisal Skills Programme checklist to ensure methodological rigor.Results: The synthesis identifies three dominant themes. Effective DEI initiatives rely on accountable leadership, high-impact practices, and sustained cultural transformation. Persistent barriers include symbolic compliance, implicit resistance, and weak evaluation systems. While psychological outcomes such as increased sense of belonging and perceived fairness are consistently reported, evidence of structural and policy-level change remains limited. DEI effectiveness is strongly associated with system-oriented and context-sensitive approaches.Conclusion and suggestion: The review concludes that DEI initiatives should move beyond isolated programs to integrate them into core organizational design and governance structures. Long-term progress requires sustained investment, justice-oriented leadership, and robust evaluation mechanisms. Future research should prioritize longitudinal analysis, cross-cultural contexts, digital and technological integration, sustainability-focused DEI models, and the development of innovative evaluation frameworks. Keywords: DEI Implementation, Diversity, Equity, Inclusion, Organizational Change, Systematic Review